Pengamanan Data Pelanggan dan Penjualan Menggunakan Implementasi Algoritma Kriptografi - Sri Vivi Wahdini; Dedy Hartama; Ika Okta Kirana; Poningsih; Sumarno (Journal of Informatics Management and Information Technology, 2021)
Data security is an important priority, as it relates to privacy, integrity, authentication, confidentiality, and customer and sales data. The confidentiality and security of customer and sales data is the most important thing in conducting business in the industrial 4.0 era, which is now all-digital. Therefore, the research objective in this paper is to secure customer data using the RSA (Rivest Shamir Adleman) cryptographic algorithm implementation. The strength and security of the RSA algorithm lie in the level of difficulty in factoring numbers into prime factors. The research in this paper uses customer data and car sales at PT. Sutan Indo Various Cars Pematangsiantar. Based on these data, a decryption encryption application will be built using the RSA algorithm. This RSA cryptographic algorithm uses a key length of 1024 bits and plaintext in the form of files with the extension Microsoft Office. The first step is to convert the plaintext and the key into hexadecimal form. The results showed that the length of the file used would affect the encryption and decryption process time. The longer the file size, the longer it will take for the encryption and decryption process. So it can be concluded that the RSA algorithm is effectively used to secure data that is not too large in file size.